Metal Telluride Nanomaterials: Facile Synthesis, Properties and Applications for Third Generation Devices. Issue 6 (11th February 2019) - Jamwal, Deepika; Mehta, Surinder Kumar
Abstract: From the material science community, metal telluride semiconductor nanostructures have lately attracted a significant quantity of attention. On account of physics associated in quantum confinement, remarkable surface chemistry metal telluride became the most explored group of semiconductor nanomaterials. The intensive concern in this area originates from their exceptional optical, chemical and electronic properties which give rise to their potential use in the field of solar energy conversion, nonlinear optics, catalysis, thermoelectric and magnetic, as well as other areas. In the current review, shape and size‐controlled synthesis strategies, substantial properties and some selected applications for metal telluride nanostructures are highlighted, for the synthesis of nanoparticles each method is favourably analyzed. Abstract : The main aim of this review is to deliver a practical guide to describe that 'in what way metal telluride nanomaterials can be prepared and developed for the future technological challenges'. Authors attempted best to tackle the chore of surveying the metal‐telluride ground, beginning through the state‐of‐art in nanoscale metal‐telluride nanomaterial preparation, covering advanced modifications, properties of them and finally the applications.